Short Communication: Biological aspects of Charybdis anisodon (De Haan, 1850) in Lasongko Bay, Central Buton, Southeast Sulawesi, Indonesia - ABDUL HAMID; YUSLI WARDIATNO (Biodiversitas Journal of Biological Diversity, 2018)
Hamid A, Wardiatno Y. 2018. Short Communication: Biological aspects of Charybdis anisodon (De Haan, 1850) in Lasongko Bay, Central Buton, Southeast Sulawesi, Indonesia. Biodiversitas 19: 1755-1762. Data on the biological aspects of Charybdis anisodon (De Haan, 1850) were still very limited. This study was aimed to determine the distribution of size, growth type, sex ratio and spawning season of C. anisodon in Lasongko Bay, Central Buton, Southeast Sulawesi. Crab collection was conducted from May 2013 to March 2014 using a crab gillnet. The carapace width of males and females C. anisodon ranged between 3.05-7.61 cm and 3.45-7.98 cm, respectively. Mann-Whitney test showed that width and length of carapace of males and females were significantly different (p<0.05). Type of growth of carapace width-body weight male and female were both allometric negative. Carapace length-body weight relationships of the males was isometric, but it was allometric negative for females. Spatially and temporally, the sex ratio of C. anisodon showed a variation, and the total sex ratio was 1: 0.38. The spawning season of C. anisodon tend to occur throughout the year.